Microbial Transformation of Flavonoids - Ciegler, Alex (1971)
The ability of a number of fungal spores, and in particular of resting vegetative mycelia, to transform naringin and naringenin was studied. In general, only hydrolytic cleavage of the sugar moieties of naringin to produce prunin and naringenin was observed. Two cultures, Penicillium charlesii and Helminthosporium sativum, also produced two unidentified flavonoid compounds but in very low yields. No transformation of aglycone was detected, although the compound was metabolized by some cultures when supplied as the glycoside prunin. A fluorodensitometric method was developed for the quantitative analysis of flavonoid compounds.